Comparative effectiveness of radical prostatectomy and curative radiotherapy in localized prostate cancer: long-term follow-up. (24th December 2016) - Tamada, Satoshi; Ninomiya, Noriko; Kitamoto, Koichiro; Kato, Minoru; Yamasaki, Takeshi; Iguchi, Taro; Ohmachi, Tetsuji; Nakatani, Tatsuya
Abstract: We sought to investigate the long-term outcomes after radical prostatectomy (RP) and external-beam radiation therapy (EBRT) for the treatment of localized prostate cancer in Japanese patients. RP and radiation therapy are curative treatments for localized prostate cancer. However, there is controversy around which treatment is superior in Japanese patients. The aim of our retrospective study was to compare the long-term clinical outcomes of each treatment. We retrospectively evaluated the overall survival (OS), cancer-specific survival (CSS) and biochemical failure–free survival (BFS) for patients who had been diagnosed with localized prostate cancer and treated with RP ( n  = 248) or conventional 2D or 3D-CRT EBRT ( n  = 182) between 1995 and 2009. The median OS was superior in the RP group compared with that in EBRT group ( P  < 0.001), although CSS was comparable for both treatment groups; BFS was superior for the EBRT group compared with that for the RP group ( P  = 0.04). Univariate analysis identified a prostate-specific antigen count (PSA)of ≥20 vs <20 mg/ml, clinical T-stage of the tumor and Gleason score as predictors for CSS. However, multivariate analysis did not identify a factor for CSS. Subgroup analysis was also performed based on clinical T stage, PSA and Gleason score, but there was no difference in each subgroup between RP and EBRT. Both treatments provided satisfactory clinical outcomes in terms of disease control in localized prostate cancer.